Penggunaan Media Pembelajaran Daring Pada Siswa Kelas 3 SD Negeri 5 Blahbatuh di Masa Pandemi COVID-19 - I Wayan Subaker; Nyoman Suryawan; Diah Nirmala Nirmala Dewi; Ni Wayan Yusi Armini (Jayapangus Press, 2022)
The COVID-19 pandemic has changed everyone's life in all aspects of life. The government has limited all community activities so that there are no crowds to avoid and break the chain of the spread of COVID-19. Based on the contents of circular letter number 15 of 2020 regarding Guidelines for Organizing Learning from Home in an emergency period of the spread of Covid-19, the Education Office of Gianyar Regency has shifted teaching and learning activities in the classroom to online or virtual learning. This phenomenon is certainly a new thing experienced by an educator and also experienced by students because they have to use online learning media as a liaison between teachers and students. The use of online learning media during the COVID-19 pandemic is an alternative choice to provide a sense of security in teaching and learning. At SD N 5 Bahbatuh, especially in grade III, the policy of the learning media used is WhatsApp. Seeing the ability of students who can only apply cellphones to WhatsApp media. Based on the results of this study, researchers can conclude that the use of learning media that is often used by teachers and preferred by students, namely WhatsApp Group is because it is easy to access and does not require a lot of quota to access it. However, as for the obstacles that students often experience when learning online during the pandemic, it is difficult to understand the subject matter, not to mention the tasks given by teachers and also parents who have busy schedules cannot always guide their children in online learning. Therefore, this online learning makes students unhappy.